Transfusion strategies in bleeding critically ill adults: A clinical practice guideline from the European Society of Intensive Care Medicine: Endorsement by the Scandinavian Society of Anaesthesiology and Intensive Care Medicine. Issue 5 (28th February 2022) - Møller, Morten Hylander; Sigurðsson, Martin Ingi; Olkkola, Klaus T.; Rehn, Marius; Yli‐Hankala, Arvi; Chew, Michelle S.
Abstract: The Clinical Practice Committee of the Scandinavian Society of Anaesthesiology and Intensive Care Medicine endorses the clinical practice guideline Transfusion strategies in bleeding critically ill adults : a clinical practice guideline from the European Society of Intensive Care Medicine . This trustworthy clinical practice guideline serves as a useful decision aid for Nordic anaesthesiologists caring for critically ill patients with bleeding.